2017
DOI: 10.4103/0259-1162.194556
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic responses at intubation, change of position, and skin incision: A comparison of multimodal analgesia with conventional analgesic regime

Abstract: Background:Lumbar spine surgery is associated with hemodynamic variations at intubation, change of position, and skin incision. A balanced anesthesia with multimodal analgesia (MMA) is necessary to attenuate these changes.Aim:To assess the relative effectiveness of preemptive MMA compared with the conventional analgesic regime in suppressing the hemodynamic response to endotracheal intubation, prone positioning, and skin incision.Settings and Design:A randomized, prospective study involving 42 patients belongi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Masahiko also studied the advantages of combining regional anaesthesia namely transversus abdominis plane block with general anaesthesia in open abdominal surgery and found the heart rate would be 70 −110% of the preanaesthetic levels in much more surgery time than those levels in patients undergoing only general anaesthesia and concluded that these advantages can be obtained with other regional anaesthetic techniques [16].…”
Section: Discussionmentioning
confidence: 99%
“…Masahiko also studied the advantages of combining regional anaesthesia namely transversus abdominis plane block with general anaesthesia in open abdominal surgery and found the heart rate would be 70 −110% of the preanaesthetic levels in much more surgery time than those levels in patients undergoing only general anaesthesia and concluded that these advantages can be obtained with other regional anaesthetic techniques [16].…”
Section: Discussionmentioning
confidence: 99%
“…In 2008, Poon et al in their study of hemodynamic changes in spine surgery in prone position demonstrated that decreased stroke volume and cardiac index are the main causes of hypotension [33]. Savitha et al described in a comparative study group that intubation and change of position need deeper plane of anesthesia compared to skin incision [34]. No positive significant responses were noted in our cases at incision.…”
Section: Discussionmentioning
confidence: 53%
“…When general anesthesia is applied, a combination of rapid sequence intubation, potentially difficult airway examination, and drugs capable to manage the hemodynamic response can help to limit the procedure's complications [5]. Alfentanil, fentanyl, remifentanil, lidocaine, and esmolol are the important drugs among them.…”
Section: Discussionmentioning
confidence: 99%